Misconceptions Among High School Students Regarding The Biological Concepts Of Human Reproduction - Salsabilla, Faulina; Melta, Defrian (Bioedunis Journal, 2024)
Understanding biological concepts is essential for integrating nature and technology into daily life. A strong grasp of these concepts enables students to develop and comprehend more advanced ideas. However, students sometimes hold interpretations that differ from scientifically accepted concepts, leading to misconceptions. The aim of this study was to identify whether misconceptions exist among students and to determine which sub-concepts in the reproductive system are most affected. Using the Certainty of Response Index (CRI) method, the study was conducted with 11th-grade students from SMAN 12 Padang. The data revealed that students had misconceptions in several sub-concepts. The highest misconception rate was in the sub-concept of menstruation at 35%, while the lowest was in the sub-concept of gamet formation at 20%. These misconceptions likely arise from students forming their own interpretations based on textbooks and teachers' explanations.Keywords: human reproduction, misconceptions, ovulation, meiosis, menstrual cycle.